Penerapan Model Blended Learning Dengan Menggunakan Google Classroom Untuk Mendukung Pemahaman Konsep Matematika Materi Perbandingan Trigonometri - Lailatus Shajidah; Suesthi Rahayuningsih; Ulil Nurul Imanah (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
This research is motivated by the limited number of studies on the implementation of the Blended Learning model utilizing Google Classroom to improve understanding of mathematical concepts, particularly in the area of trigonometric ratios. This gap is important because it significantly impacts students' ability to understand concepts and apply them in problem-solving scenarios. The purpose of this study is to evaluate the use of the Blended Learning model through Google Classroom, as well as student engagement and understanding of mathematical concepts related to trigonometric ratios. This research was conducted using a quantitative descriptive approach involving 13 10th-grade vocational high school students, with a One-Shot Case Study design. Data collection was conducted by observing teacher and student activities, as well as administering a conceptual understanding test. Findings from the observations indicate that the implementation of the learning process by the teacher achieved a score of 90.63%, which is categorized as "Very Good". Student engagement, as assessed through six random samples, exceeded 88.33%, which is categorized as "Very Active", both in online learning sessions through Google Classroom and face-to-face interactions. The conceptual understanding test results showed that 15.38% of students were in the "Very High" category, while 84.62% of students were in the "High" category, with a classical completion rate of 100%. These findings indicate that the Google Classroom-based Blended Learning model effectively encourages active student participation and supports their understanding of mathematical concepts. Abstrak Penelitian ini berangkat dari masih minimnya kajian mengenai penerapan model Blended Learning dengan menggunakan Google Classroom dalam mendukung pemahaman konsep matematika, terutama pada materi perbandingan trigonometri. Kondisi tersebut berdampak signifikan terhadap kemampuan siswa dalam menguasai konsep sekaligus menggunakannya untuk menyelesaikan masalah. Oleh karena itu, penelitian ini bertujuan mendeskripsikan penerapan model Blended Learning dengan menggunakan Google Classroom, menganalisis aktivitas siswa, serta menilai pemahaman konsep matematika pada materi perbandingan trigonometri. Penelitian dilakukan dengan metode kuantitatif deskriptif pada 13 siswa kelas X di salah satu SMK, menggunakan desain One Shot Case Study. Data dikumpulkan melalui observasi aktivitas guru dan siswa, serta tes pemahaman konsep. Hasil observasi menunjukkan keterlaksanaan pembelajaran oleh guru sebesar 90,63% (kategori “Sangat Baik”). Aktivitas siswa pada enam sampel acak berada di atas 88,33% (kategori “Sangat Aktif”), baik dalam pembelajaran daring di kelas menggunakan Google Classroom maupun tatap muka. Tes pemahaman konsep menunjukkan 15,38% siswa berada pada kategori “Sangat Tinggi” dan 84,62% pada kategori “Tinggi” dengan ketuntasan klasikal 100%. Hasil ini menunjukkan bahwa model Blended Learning dengan menggunakan Google Classroom dapat mendukung keterlibatan aktif siswa dan pemahaman konsep matematika. Kata Kunci: Blended Learning, Google Classroom, aktivitas siswa, pemahaman konsep, perbandingan trigonometri.